Peran Kaum Muda dalam Meningkatkan Iman Melalui Katekese - Jebar, Sirilus; Darmingtri, Yonas; Melo, Paulus; B. Lena Meo, Yohanes Wilson (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
This article discusses the role of catechesis in the proclamation of the faith of the Catholic Church, with a focus on youth participation. Catechesis is a form of faith proclamation, with the center being the development and proclamation of faith values about Jesus Christ. This article aims to highlight the relevance of the role of young people in catechesis, as well as the objectives and methods of the proclamation of faith carried out through catechesis. The author uses a methodology through theological reflection, taking into account various aspects of the spiritual life of Catholics such as the experience of God and the understanding of Church teachings. The findings of this article emphasize the important role of young people in the proclamation of faith, both personally and communally. Catechesis is considered an important tool in honing and strengthening the faith of young people, as well as helping them take an active part in proclaiming the teachings of the faith. The novelty of this article is the emphasis on the existence of young people as the vanguard of the Church, who have great potential to bring change and renewal in proclaiming the faith. The relevance of this article lies in the urgency of paying attention to the role of young people in catechesis as an integral part of the Church's mission, as well as the importance of facilitating and supporting their participation in the proclamation of the faith.